2011
DOI: 10.1002/ibd.21460
|View full text |Cite
|
Sign up to set email alerts
|

Distinct microbiome in pouchitis compared to healthy pouches in ulcerative colitis and familial adenomatous polyposis

Abstract: The pouch microbial environment appears to be distinctly different in the settings of UC pouchitis, healthy UC, and FAP. These findings suggest that a dysbiosis may exist in pouchitis which may be central to understanding the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…242 The other study analyzed the FAM and MAM of UC patients with and without pouchitis compared with Familial Adenomatous Polyposis pouches and found that UC pouchitis patients had substantially fewer Bacteroidetes and more Clostridia compared to the healthy UC pouch and Familial Adenomatous Polyposis groups. 243 …”
Section: Pouchitismentioning
confidence: 97%
“…242 The other study analyzed the FAM and MAM of UC patients with and without pouchitis compared with Familial Adenomatous Polyposis pouches and found that UC pouchitis patients had substantially fewer Bacteroidetes and more Clostridia compared to the healthy UC pouch and Familial Adenomatous Polyposis groups. 243 …”
Section: Pouchitismentioning
confidence: 97%
“…Although created from small intestinal tissue, the microbiota of the pouch frequently resembles that of the colon. 122 Like UC itself, however, patients with pouchitis may have a pouch microbiota that is distinct from that of patients without active inflammation. 122,123 Although this suggests that FMT may also be a treatment of pouchitis, small studies have failed to demonstrate remission following FMT.…”
Section: Pouchitismentioning
confidence: 99%
“…122 Like UC itself, however, patients with pouchitis may have a pouch microbiota that is distinct from that of patients without active inflammation. 122,123 Although this suggests that FMT may also be a treatment of pouchitis, small studies have failed to demonstrate remission following FMT. 124 One key limitation in FMT for pouchitis is the size of the pouch, which may limit engraftment of a donor microbiota.…”
Section: Pouchitismentioning
confidence: 99%
“…Only now, with the increasing number of animal microbiome data available, are we beginning to understand the nature of microbiome plasticity in animals [85,170]. With recent studies on the relative contributions of factors such as host genetics [128,170], diet [171], environmental exposure [87] and health [172], we are now poised to venture toward a quantified understanding of microbiome evolution. It is clear that a multifaceted approach is the only way we can hope to understand how a microbiome evolves and adapts along inter-and intra-specific axes, along with the varying contributions of polygenic traits on the abundance and interactions of individual microbial species, related taxa, and groups of distantly related organisms.…”
Section: Perspectivementioning
confidence: 99%